Pengaruh Kompetensi Dan Penempatan Kerja Terhadap Kinerja Pegawai Negeri Sipil - Dian Sudiantini; Raffa Calysta Suhatman; Rigel Ken Meilizar; Ringga Jati Ismawan; Salwa Aristawidya (Pusat Riset dan Inovasi Nasional, 2023)
Each agency in carrying out its activities has goals that must be achieved. To achieve or realize these goals, each agency must be good at choosing strategies, especially there is human resource planning which in essence is focused on certain steps taken by management. For the availability of a permanent workforce to occupy the position and the right time in order to achieve the goals and various targets set. Employee placement is expected to make an adequate contribution to the organization in addition to being an effort to develop human resource competencies in the organization. With improper placement, a person's performance will not match the expectations of management and organizational demands, thus they display low work productivity which can result in boredom and boredom. Theoretically, the placement of employees in an organization must have an adjustment between the qualifications or educational background of employees with the qualifications of the job they will carry. To find out whether the placement process is successful or not, what the company can do is to evaluate employee behavior and work performance in the form of a work presentation assessment. The ability of employee resources is often hampered if faced with job placement problems.